2022
DOI: 10.1101/2022.08.26.505496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale mapping and systematic mutagenesis of human transcriptional effector domains

Abstract: Human gene expression is regulated by over two thousand transcription factors and chromatin regulators. Effector domains within these proteins can activate or repress transcription. However, for many of these regulators we do not know what type of transcriptional effector domains they contain, their location in the protein, their activation and repression strengths, and the amino acids that are necessary for their functions. Here, we systematically measure the transcriptional effector activity of >100,000 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 60 publications
3
68
0
Order By: Relevance
“…( J ) Gene silencing dynamics of the dual effector tile from EBV MTP highlighted in (H) upon recruitment at the pEF reporter: mCitrine levels initially increase in all cells, then subsequently bifurcate, with one population maintaining elevated mCitrine levels relative to the no dox sample and the other silencing completely by day 5 of recruitment. These dynamics are observed for several validated dual effector tiles (data not shown) and are similar to those observed for a set of dual effectors tiles from human transcription factors, albeit at a different promoter 32 . ( K-L ) Scatterplot of the average activation (K) or repression (L) screen scores for tiles shared between the vTR and herpesvirus (HHV) libraries.…”
Section: Supplemental Figuressupporting
confidence: 76%
See 1 more Smart Citation
“…( J ) Gene silencing dynamics of the dual effector tile from EBV MTP highlighted in (H) upon recruitment at the pEF reporter: mCitrine levels initially increase in all cells, then subsequently bifurcate, with one population maintaining elevated mCitrine levels relative to the no dox sample and the other silencing completely by day 5 of recruitment. These dynamics are observed for several validated dual effector tiles (data not shown) and are similar to those observed for a set of dual effectors tiles from human transcription factors, albeit at a different promoter 32 . ( K-L ) Scatterplot of the average activation (K) or repression (L) screen scores for tiles shared between the vTR and herpesvirus (HHV) libraries.…”
Section: Supplemental Figuressupporting
confidence: 76%
“…5A). Many eukaryotic transcriptional activation domains consist of interspersed acidic and hydrophobic residues [29][30][31] , while repressors fall into more categories not defined by common sequence composition 32 . In line with this, nearly all activator tiles from the HHV tiling screen have a net negative charge, with stronger activator tiles typically having greater negative charge (Fig.…”
Section: Sequence Analyses and Systematic Perturbation Of Herpesvirus...mentioning
confidence: 99%
“…Normalization of mCitrine levels to the no-dox condition was performed as follows: f off,norm = ( f off,dox – f off,no dox ) Ă· (1 – f off.no dox ) where f off denotes the fraction of cells off for any given condition. Cytometry analysis was otherwise performed identically as in 20,21 .…”
Section: Methodsmentioning
confidence: 99%
“…Although recruitment assays have historically focused on recruiting only one transcriptional effector per cell, combinatorial function is a key property of both chromatin-mediated gene regulation 16 and transcription factor-mediated gene regulation [17][18][19] . Transcription factors frequently contain multiple effector domains with potentially opposing functions, with studies reporting up to 40% of transcription factors having at least 2 distinct effector domains 2,20 . For example, the chromatin regulator MGA was recently shown to feature two repressive domains with different rates of silencing and amounts of memory 21 , while an earlier study showed that the transcription factor NIZP1 features an activating KRAB domain that is dominated by a repressive C2HR domain 22 .…”
Section: Main Text Introductionmentioning
confidence: 99%
“…Other RDs may utilize entirely different sets of CoRs than the ones found and studied here. A recent study that maps RDs in human proteins (preprint: DelRosso et al , 2022 ) implicates short SUMOylation sites and SUMO interacting motifs in RD function, consistent with a role of SUMOylation in transcriptional repression (Ross et al , 2002 ; Rocca et al , 2017 ; Ninova et al , 2020 ; Andreev et al , 2022 ). We also find SUMOylation and SUMO interaction sites in RDs (Dataset EV8 ), but these motifs do not occur significantly more frequently in RDs than in other non‐RD fragments tested in the screen (Dataset EV8 ), presumably because such sites are short and/or have low information content and because SUMOylation may not be exclusively used in RDs.…”
Section: Discussionmentioning
confidence: 68%